ANALISIS TINGKAT KESEHATAN BANK PADA PT. BANK JTRUST INDONESIA TBK DENGAN METODE RISK BASED BANK RATING (RBBR) TAHUN 2014 - 2018 - Agil Untung Hariyono, Mardiana dan Danna Solihin (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2021)
The research is aimed to investigate and analyze the soundness of commercial banks, based on Financial Services Authority Circular Letter Regulation No. 14/SEOJK.03/2017. The sample in this study was PT. Bank JTrust Indonesia Tbk, period 2014-2018. The analytical tool used is the Bank's health report on factors that use the net performing loan (NPL) ratio and the ratio of loans to deposits (LDR), corporate governance factors using self-assessment reports of good corporate governance (GCG), profitability factors with using the ratio of return on assets (ROA) and net interest margin (NIM) and capital factors using the capital adequacy ratio (CAR).The results of this study indicate that from the results of the study, commercial banks, commercial banks with results that are less healthy and unhealthy. Based on the NPL ratio in 2014 with unhealthy results, based on the LDR ratio in 2016 and 2017 with fairly healthy results. Based on the factors of corporate governance / GCG in 2014 the results of the assessment were not good.Based on the ROA ratio in 2014, 2015, 2016 and 2018 with unhealthy results and in 2017 with fairly healthy results. Based on the NIM ratio in 2014 with Unhealthy results and in 2015 with Unhealthy Results. And based on the CAR ratio of all banks in the healthy category (very healthy, healthy, quite healthy).